2021
DOI: 10.37287/jppp.v3i3.523
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan tentang Covid-19 Berhubungan dengan Kepatuhan Keluarga Memakai Masker di IGD Rumah Sakit

Abstract: Pengunjung yang datang di Instalasi Gawat Darurat Rumah Sakit masih banyak yang tidak menggunakan masker atau menggunakan masker tetapi tidak benar. Penelitian bertujuan untuk mendapatkan hubungan pengetahuan tentang COVID-19 dengan kepatuhan memakai masker di IGD. Pengambilan sampel dilakukan dengan menggunakn teknik accidental sampling dengan jumlah 70 orang. Instrumen yang digunakan adalah kuesioner tentang COVID-19 dan lembar observasi kepatuhan memakai masker. Data dianalisis secara univariat menggunakan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
5
0
6
Order By: Relevance
“…High knowledge is expected to increase compliance. As age increases, a person's knowledge and comprehension ability will increase (Hutapea and Soputri, 2021). One of the important things that the public must pay attention to is knowledge, especially to prevent transmission of the Covid_19 virus through vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…High knowledge is expected to increase compliance. As age increases, a person's knowledge and comprehension ability will increase (Hutapea and Soputri, 2021). One of the important things that the public must pay attention to is knowledge, especially to prevent transmission of the Covid_19 virus through vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…28 Other studies show found a significant relationship between knowledge about COVID-19 and adherence to wearing masks. 29 Knowledge of how to achieve health care, and how to avoid disease, will increase public knowledge. 30 According to Sari and 'Atiqoh (2020) 31 there is a relationship between public knowledge and compliance with the use of masks as an effort to prevent Covid-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that good knowledge will support positive attitudes about the COVID-19 vaccine. Hutapea MA et al 20 stated that there was a relationship between knowledge and willingness to do the vaccine (P = 0.002). Decision-making is influenced by knowledge so that beneficial actions for individuals are formed, including the willingness to be vaccinated against COVID-19.…”
Section: Originalmentioning
confidence: 99%
“…This could be due to the different research times. Research Hutapea M et al 20 will be carried out in 2021, while our research will be carried out in 2022 and 2023. The one-year time difference will allow the government to socialize and increase information regarding the COVID-19 vaccination to the community.…”
Section: Originalmentioning
confidence: 99%